Graphene Oxide‐Cyclic R10 Peptide Nuclear Translocation Nanoplatforms for the Surmounting of Multiple‐Drug Resistance. (26th June 2020) - Tu, Zhaoxu; Donskyi, Ievgen S.; Qiao, Haishi; Zhu, Zhonglin; Unger, Wolfgang E. S.; Hackenberger, Christian P. R.; Chen, Wei; Adeli, Mohsen; Haag, Rainer
Abstract: Multidrug resistance resulting from a variety of defensive pathways in cancer has become a global concern with a considerable impact on the mortality associated with the failure of traditional chemotherapy. Therefore, further research and new therapies are required to overcome this challenge. In this work, a cyclic R10 peptide (cR10 ) is conjugated to polyglycerol‐covered nanographene oxide to engineer a nanoplatform for the surmounting of multidrug resistance. The nuclear translocation of the nanoplatform, facilitated by cR10 peptide, and subsequently, a laser‐triggered release of the loaded doxorubicin result in efficient anticancer activity confirmed by both in vitro and in vivo experiments. The synthesized nanoplatform with a combination of different features, including active nucleus‐targeting, high‐loading capacity, controlled release of cargo, and photothermal property, provides a new strategy for circumventing multidrug resistant cancers. Abstract : Cyclic R10 peptide (cR10 )‐functionalized polyglycerol‐covered nanographene oxide (nGO) sheets are designed for the treatment of multi‐drug resistant tumors. The nucleus accumulation of functionalized nGO is guided by cR10 and the controlled release of loaded therapeutic agents is triggered by near‐infrared laser. Both in vitro and in vivo experiments confirm the efficient anticancer therapeutic effect of these nucleus‐targeting nanoplatforms.